Karyotype analysis with orcein and CMA from leaf base cells of Rauvolfia serpentina Benth. et Kurz (Bangladesh Journal of Botany, 2010)
Many prominent darkly stained heterochromatic blocks were found in the interphase nuclei of Rauvolfia serpentina following orcein staining. The prophase chromosomes of this species became stained homogeneously throughout the entire length. This species was found to possess 2n = 20 metacentric chromosomes revealing symmetric karyotype but if the chromosome length (6.67 - 3.17 μm) is considered, it indicates asymmetric karyotype. Total GC-rich region was 15.62% of the total chromatin length. Eight CMA-positive bands on different locus revealed the accumulation of GC-rich repeats. The two entirely CMA-banded chromosomes were so unique that could be used as marker for this species. Key words: Karyotype; Rauvolfia serpentina; Fluorescent banding DOI: 10.3329/bjb.v38i1.5133 Bangladesh J. Bot. 38(1): 55-63, 2009 (June)